Analysis of Student Online Interaction Behavior: A Social Relationship Perspective - Peiyan Yuan; Hai Yu; Ping Liu (European Alliance for Innovation (EAI), 2018)
Mobile opportunistic networks (MONs) have been attracting increasing amounts of attention in recent years. Characterizing user contact behavior provides a baseline to evaluate the performance of these networks. However, because the contact distribution of nodes in MONs is conventionally modeled from a large-scale perspective, i.e., by aggregating all node pairs, the contact features of nodes with multiple social relationships are not reflected. Thus, it is not clear whether friends and strangers have similar or different contact behaviors. In this study, we aggregated the contact information of users from the real world, and discovered that two phenomena exist: (1) Most friends or strangers make contact at public hotspots, rather than private hotspots; (2) The distribution of intra-contact time (ICT) exhibits different decay factors---the ICT distribution of strangers is predominantly faster than that of friends.